DOI: 10.14264/uql.2015.847
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing for multi-scale mangrove mapping

Abstract: Understanding the relationships between the size of mangrove vegetation features and the optimum image pixel size required to map these features is essential to support effective mapping and monitoring activities in this environment. Currently mangroves are under pressure from anthropogenic and natural disturbances, and up-to-date and accurate spatial information is required to support their management. Addressing ecological problems at the correct spatial scale is essential in mangrove environments. There is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 179 publications
(401 reference statements)
0
5
0
Order By: Relevance
“…Some of the characteristics of mangroves that are used as keys to remote sensing interpretation are mangrove location, zoning patterns, canopy texture characteristics, and canopy's spectral reflectance characteristics [16]. Heenkenda et al [17] stated that there are two challenges in mapping wetland vegetation (including mangroves) using remote sensing techniques.…”
Section: Mangrove Identificationmentioning
confidence: 99%
“…Some of the characteristics of mangroves that are used as keys to remote sensing interpretation are mangrove location, zoning patterns, canopy texture characteristics, and canopy's spectral reflectance characteristics [16]. Heenkenda et al [17] stated that there are two challenges in mapping wetland vegetation (including mangroves) using remote sensing techniques.…”
Section: Mangrove Identificationmentioning
confidence: 99%
“…where: = measured carbon stock, = carbon stock estimation, ̅ = average measured carbon stock (Weng, 2010a;Chuvieco et al, 2010;(Köhlet al, 2006)Vicharnakorn et al, 2014Kamal, 2015;Alparone et al, 2015;Thenkabail, 2016;Alan et al, 2017;)…”
Section: Methodsmentioning
confidence: 99%
“…This result was different from the Sentinel-2 imagery (published in Muhsoniet al, 2018) at 0.247056 ton 100m -2 , although the best vegetation index corresponded to NNIP. Kamal (2015) performed a study in Karimunjawa using Landsat TM imagery, and showed SR as the best index, with RMSE of 1.23 ton 900m -2 . Meanwhile, SPOT 5 and Landsat TM were used by Hamdanet al (2013) and NDVI was obtained as superior, alongside the adoption of non-linear regression.…”
Section: Carbon Content Modeling Of Mangrove Vegetation Using Ldcm Imagerymentioning
confidence: 99%
“…The selection of sample location was guided by WorldView-2 pan-sharpened image (0.5m pixel size), that is by identifying accessible Rhizophora stylosa at the edge of the mangrove forest where measurement of spectral reflectance at different distance can be performed. From previous research [27] Avicennia marina, Rhizophora stylosa, Bruguiera gymnorrhiza, and Lumnitzera racemosa can be distinguished by visual interpretation of WV-2 images because they have specific canopy patterns and clustered at specific locations. From this site, a single sampling point was taken purposively based on the availability of target species and measured at several distances.…”
Section: Field Spectral Reflectance Measurementmentioning
confidence: 97%